Bandgap Engineering of Amorphous Hydrogenated Silicon Carbide - Guerra J.A. (2016)
This research was funded by the Research Management Office (DGI) of the Pontificia Universidad Católica del Perú (PUCP). The authors have been supported by the PUCP under the PhD scholarship program Huiracocha (J A Guerra) and by the National Council of Science and Technology (CONCYTEC) under the scholarships granted to the PUCP (J R Angulo and J Llamoza). The author would like to thank Prof Dr H P Strunk, F Benz and Dr Y Weng of the University of Stuttgart for the TEM measurements.